KEANEKARAGAMAN PLANKTON DANAU SIOMBAK KECAMATAN MEDAN MARELAN KOTA MEDAN The Diversity of Plankton at Siombak Lake, Medan Marelan District of Medan City - Supardi Harahap; Hesti Wahyuningsih; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Siombak Lake is an artificial lake located in Kelurahan Rengas Pulau, Medan Marelan, is 18 km north of the center of Medan. Plankton is one of the main components in the food chain and food web. The purpose of this research is to know the diversity of plankton community, the value of water chemistry physics parameters, and the correlation between water chemical physics factor with plankton at Lake Siombak Medan Marelan Sub-district Medan City. The research was conducted at Siombak Lake in September 2015. Plankton and plankton water quality data including temperature, pH, brightness, dissolved oxygen (DO), BOD5, NH3, and phosphor grades were obtained from the field and analyzed in the laboratory. The method used in determining the sampling location for plankton sampling is